2000
DOI: 10.1007/s004670050005
|View full text |Cite
|
Sign up to set email alerts
|

Intraperitoneal pressure and hernias in children on peritoneal dialysis

Abstract: Abdominal wall hernias have been increasingly recognized in patients on continuous ambulatory peritoneal dialysis (CAPD). They are also more frequent in children than in adults. The aim of this study was to determine the influence of intraperitoneal pressure (IPP) on the development of hernias in children on CAPD, and if there was a difference between IPP in children and adults. We studied 14 children aged 11.2 +/- 3.2 years, body weight 31.1 +/- 9.4 kg, who had undergone CAPD for 16.2 +/- 14.4 months. Also, 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
1
1

Year Published

2003
2003
2022
2022

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(18 citation statements)
references
References 16 publications
1
15
1
1
Order By: Relevance
“…Although Dejardin et al demonstrated a positive correlation between higher body mass index, larger dialysate volume and higher IPP (10), an association between the level of IPP and the risk of hernia in PD patients is still controversial. An increased IPP has been shown to correlate with the development of hernias in PD patients (9,17), yet other studies have not reported a correlation between IPP, dialysate volume and the risk of hernia formation (2,3,7,10). In our study, after the logistic regression analysis, a larger maximal dialysate volume was not significantly related to the risk of hernia formation, which further supports the idea that increased IPP alone may not increase the risk of hernia formation.…”
Section: Discussionmentioning
confidence: 99%
“…Although Dejardin et al demonstrated a positive correlation between higher body mass index, larger dialysate volume and higher IPP (10), an association between the level of IPP and the risk of hernia in PD patients is still controversial. An increased IPP has been shown to correlate with the development of hernias in PD patients (9,17), yet other studies have not reported a correlation between IPP, dialysate volume and the risk of hernia formation (2,3,7,10). In our study, after the logistic regression analysis, a larger maximal dialysate volume was not significantly related to the risk of hernia formation, which further supports the idea that increased IPP alone may not increase the risk of hernia formation.…”
Section: Discussionmentioning
confidence: 99%
“…However, infants with limited abdominal wall, particularly if hypoproteinemic, are at risk of distal cuff extrusion [14], with a subsequent higher risk of leakage, exit site infection, and eventually peritonitis. This risk can be reduced by delaying dialysis onset to 2-3 weeks after implantation and by monitoring intraperitoneal pressure [15,16]. Concerns also exist that a downward exit site may be a risk factor for infections in small children using diapers.…”
Section: What We Knowmentioning
confidence: 99%
“…They can be avoided by delaying the onset of dialysis to 2-3 weeks after implantation and by IPP monitoring [56][57][58].…”
Section: Complicationsmentioning
confidence: 99%